Does Movement Matter? Motor Activity Stimulation for Children with Autism Spectrum Disorder - Firda Ruhyah Mau’izhah; Nur Faizah Romadona; Heny Djoehaeni (Murhum : Jurnal Pendidikan Anak Usia Dini, 2026)
This review aimed to synthesize empirical evidence regarding motor activity stimulation in young children with ASD, including intervention forms, developmental impacts, and implementation challenges. A Systematic Literature Review (SLR) method was selected to synthesize empirical evidence regarding motor activity stimulation in children with ASD and was conducted using the PRISMA 2020 flow diagram. Of 251 articles identified through Scopus and supporting databases, 13 empirical studies involving children with ASD aged 2–6 years published between 2021 and 2026 were selected and analyzed. The findings indicated that motor activity stimulation was implemented through fundamental movement activities, sensorimotor training, social-motor activities, and daily routines across home, school, therapy, and structured sports contexts. The findings also demonstrated contributions to motor development, sensory regulation, social interaction, behavior, and children’s independence. However, implementation still faced challenges related to limited understanding among teachers and parents, as well as insufficient institutional support. This review showed that motor activity stimulation in children with ASD was not only associated with motor abilities, but also with sensory regulation, social skills, and participation in daily activities. Multimodal and contextual approaches were needed to support children’s development according to their individual needs.